Metal–Organic Frameworks – Heading towards Application. Issue 27 (27th September 2016) - Dietzel, Pascal D. C.; Kitagawa, Hiroshi
Abstract : Guest Editors Pascal Dietzel and Hiroshi Kitagawa give an overview of the papers clustered together in this issue on metal–organic frameworks with emphasis on applications.